Regenerative Cells in the Midgut of the Honey Bee Apis mellifera (Apidae: Apini) Queens with Different Ages - Werônica Célia Stalino Dias; Érica Weinstein Teixeira; José Eduardo Serrão (Brazilian Archives of Biology and Technology, 2024)
Abstract The honey bee Apis mellifera is a plant-pollinator that produces commercial products. It has female castes with workers performing tasks in the colonies and a queen, it has the longest lifespan, in charge of reproduction. This bee undergoes a population decline worldwide. Therefore, it is important to understand how aging affects the digestive tract of this insect. In the midgut, regenerative cells are organized in nests replacing the dead cells. This study verified the hypothesis that the number of regenerative cells decreases as A. mellifera queen ages. The midgut was evaluated in queens at the age of four days and eight, 11 and 25 months. The midgut of 11- and 25-month-old queens presented signs of epithelial disorganization in comparison with younger queens. The number of regenerative cell nests in the midgut decreases according to the age of the queen, but the number of cells per nest is similar. The decreased number of regenerative cell nests reveals a potential loss in the amount of these cells available for the renewal of the midgut epithelium. The absence of variations in the number of regenerative cells per nest according to the queen age indicates that these cells do not undergo proliferation before the differentiation.